Understanding Second-hand Smoke (SHS) exposure among university students in Selangor and Perak, Malaysia: role of parents and peers / Siti Mariana Anis binti Saberi ... [et al.] - Saberi, Siti Mariana Anis; Syed Putera, Syarifah Syamimi Putri Adiba; Zulkifly, Hanis Hanum; Abdul Halim Zaki, Izzati; Md Hussin, Nur Sabiha; Mohd Noordin, Zakiah (Faculty of Pharmacy, 2023)
Second-hand smoke (SHS) exposure remains a significant public health concern worldwide, posing various adverse effects on individual health during both short- and long-term exposures. University students in Malaysia are particularly at risk due to the potential influence of parents and peers on their SHS exposure. However, there is a lack of comprehensive research exploring the extent of this influence and its implications for effective intervention strategies. This cross-sectional study administered an online questionnaire to 387 students from two universities in Selangor and Perak. Prevalence rates of SHS exposure were determined, and factors associated with exposure were identified through descriptive and multivariable logistic regression analysis. Almost half (49.9%) of the participants had been exposed to SHS. Female students had a reduced risk of exposure by more than half compared to male students (p = 0.050). Meanwhile, those who had a smoking parent and smoking friends had approximately four times (p = 0.000) and two times (p = 0.002) the increased likelihood of being exposed to SHS, respectively, then those who did not. Participants with higher household income (p = 0.000) and higher mothers' educational attainment (p = 0.028) had a significantly lower risk of SHS exposure. In conclusion, gender, parental smoking, peer smoking, and socioeconomic status were identified as factors associated with SHS exposure. Parental and peer awareness and understanding of SHS risk must be enhanced to minimise its exposure among their children and friends. Hence, health policymakers should address strategies such as ongoing public awareness campaigns, the extension of a smoking ban on advertising, promotion, and marketing of tobacco products, and rules for smoking prohibition at home to drive Malaysia's effort towards a smoke-free generation.